Fungal community on decomposing leaf litter undergoes rapid successional changes - Voříšková, Jana; Baldrian, Petr (The ISME journal, 2013)
Fungi are considered the primary decomposers of dead plant biomass in terrestrial ecosystems. However, current knowledge regarding the successive changes in fungal communities during litter decomposition is limited. Here we explored the development of the fungal community over 24 months of litter decomposition in a temperate forest with dominant Quercus petraea using 454-pyrosequencing of the fungal internal transcribed spacer (ITS) region and cellobiohydrolase I (cbhI) genes, which encode exocellulases, to specifically address cellulose decomposers. To quantify the involvement of phyllosphere fungi in litter decomposition, the fungal communities in live leaves and leaves immediately before abscission were also analysed. The results showed rapid succession of fungi with dramatic changes in the composition of the fungal community. Furthermore, most of the abundant taxa only temporarily dominated in the substrate. Fungal diversity was lowest at leaf senescence, increased until month 4 and did not significantly change during subsequent decomposition. Highly diverse community of phyllosphere fungi inhabits live oak leaves 2 months before abscission, and these phyllosphere taxa comprise a significant share of the fungal community during early decomposition up to the fourth month. Sequences assigned to the Ascomycota showed highest relative abundances in live leaves and during the early stages of decomposition. In contrast, the relative abundance of sequences assigned to the Basidiomycota phylum, particularly basidiomycetous yeasts, increased with time. Although cellulose was available in the litter during all stages of decomposition, the community of cellulolytic fungi changed substantially over time. The results indicate that litter decomposition is a highly complex process mediated by various fungal taxa.
Keywords: Biodiversity; listy rostlin; stromy; Fungi; Quercus; fylogeneze; Phylogeny; Trees; biodiverzita; houby; Soil Microbiology; analýza hlavních komponent; mezerníky ribozomální DNA; Principal Component Analysis; Plant Leaves; dub (rod); půdní mikrobiologie; Cellulose 1,4-beta-Cellobiosidase; DNA, Ribosomal Spacer; celulosa-1,4-beta-cellobiosidasa